Contemporary oasis hydraulics: An open window on the sociology of the population of medieval Saharan cities - Chloé Capel (Afriques)
This paper compares two fields of analysis: on the one hand, hydrosociology, theorized by geographers and anthropologists, which conceptualizes the uses and landscapes of water as a reflection of the social organization of the group; on the other hand, hydraulic archaeology, developed by archaeologists and historians, which has demonstrated the permanence of ancient hydraulic structures in contemporary landscapes. The aim of this cross-disciplinary approach is to produce a social interpretation of the ancient irrigation systems fossilized in current agricultural plots, in order to produce a diachronic analysis of social organizations that have disappeared. The case study of this contribution deals with the medieval city of Sijilmasa (Morocco) and the Saharan oasis of Tafilalt that still surrounds the archaeological site today. This study of sub-contemporary oasis hydraulics has made it possible to historicize its development over the long term and to highlight a clear correlation between the successive implementations of different irrigation practices and the evolution of the socio-political organization of the Tafilalt population over the centuries. Corroborated by textual sources, this model could be applied in the future to other medieval Saharan oases for which no written or archaeological record remains and whose social organization is otherwise unknown.